Clinical Urologic Endocrinology Principles for Men's Health - Kavoussi, Parviz K.; Costabile, Raymond A.; Salonia, Andrea (Springer London : Imprint: Springer, 2013)
Clinical Urologic Endocrinology: Principles for Men's Health provides an organized, accessible reference on men's endocrinological health.   Over 30 million men in the US alone suffer from erectile dysfunction and over 13 million men in the US suffer from hypogonadism (low testosterone). One out of seven couples also suffer from subfertility of which 50-60% have male factor involvement. More and more men are coming forward to seek treatment for such issues, which in the past were considered taboo and there is a strong need for a book which provides guidance for practitioners who support men in their reproductive and sexual concerns. This book covers in depth the key issues in male reproductive health in one easy-to-use resource.    Clinical Urologic Endocrinology: Principles for Men's Health is a valuable reference for urologists, endocrinologists, internal medicine physicians, family medicine physicians, sex therapists, and allied health professionals providing care for men in the areas of sexual health, fertility, and men's endocrinological health. .